2007
DOI: 10.1111/j.1600-9657.2005.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Dento‐alveolar and maxillofacial injuries – a retrospective study from a level 1 trauma center in Israel

Abstract: To evaluate the frequency and causes of dental and maxillofacial trauma in hospitalized patients. From January 1, 2000 to December 31, 2003, data from hospitalized trauma patients in a level 1 trauma center in Israel were analyzed according to age, gender, time, place, and cause of injury. Maxillofacial and tooth injuries were separated and further analyzed according to the above parameters. The analysis was based on data from the Israel Trauma Registry (ITR). Of all 14 040 trauma patients, 1038 (7.4%) involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 12 publications
(12 reference statements)
8
20
1
7
Order By: Relevance
“…The age distribution in this study showed that the most common age group involved was 19 and 28 years, in agreement with previous reports 5,10,11,13,15 . The highest incidence in this age group is due to the fact that this age group take part in dangerous exercises and sports, drive motor vehicles carelessly, and are most likely to be involved in violence 4,16 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The age distribution in this study showed that the most common age group involved was 19 and 28 years, in agreement with previous reports 5,10,11,13,15 . The highest incidence in this age group is due to the fact that this age group take part in dangerous exercises and sports, drive motor vehicles carelessly, and are most likely to be involved in violence 4,16 .…”
Section: Discussionsupporting
confidence: 82%
“…The sex distribution in the present study is consistent with that of others, with a higher frequency of craniomaxillofacial fractures in males compared with females [4][5][6]9,11,13,14 . This study found a higher male-to-female ratio (8.3:1) than was noted in previous study in Chennai 7 (3.7:1), in Tehran 1 (4.5:1) and in United Arab 10 (7:1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, there was a high frequency of injuries in participants aged 21-30 years (26.18%), which is in agreement with the results obtained in other studies [3,6,7,17,[20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…These findings corroborate the results obtained by Gassner et al [3], Ribeiro et al [15], Lin et al [20], Pereira et al [18] Several factors may influence the relationship between gender and maxillofacial trauma, such as the socioeconomic and cultural characteristics of the sample [1,17]. In general, males are more involved in traffic accidents and physical contact activities without the use of adequate protection [7].…”
Section: Discussionsupporting
confidence: 90%